Outdoor human thermal comfort in local climate zones of Novi Sad (Serbia) during heat wave period - MiloševićDragan D.; SavićStevan M.; Marković, Vladimir; Arsenović, Daniela; Šećerov, Ivan (Hungarian Geographical Bulletin, 2016)
Urban climate monitoring system (UCMS) was established in Novi Sad (Serbia) in 2014 based on the Local Climate Zones (LCZs) classification system, GIS model calculations and field work. Seven built and two land cover LCZ types were delineated and 27 stations equipped with air temperature and relative humidity sensors were distributed across all LCZs. Suitability of the developed monitoring system for human outdoor thermal comfort research in different LCZs of the city and its surroundings was investigated during a heat wave period using Physiologically Equivalent Temperature (PET) index. During the daytime (night-time) the highest thermal loads are present in open midrise (compact midrise) LCZ, while the most comfortable is LCZ A (dense trees) during the whole day. In general, the highest thermal loads are obtained in midrise, followed by low-rise, sparsely built, low plants and dense trees LCZs. All LCZs (except LCZ A - dense trees) had higher PET when compared to LCZ D (LCZ D - low plants) during evening and nocturnal hours with maximum difference of 7.1 °C (00 UTC) between LCZ 2 (compact midrise) and LCZ D (low plants). Contrary to this, LCZ D (low plants) had higher PET compared to the majority of LCZs during the daytime with maximum difference of 8.5 °C (9 UTC) when compared to LCZ A (dense trees). Furthermore, the smallest thermal comfort differences during heat wave occurred between LCZs with similar structure (i.e. open low-rise and large low-rise, compact midrise and compact low-rise) and cover (i.e. sparsely built and low plants).